Audição e equilíbrio: investigação em mulheres na pósmenopausa - Bellé, Marcieli (2007)
The maintenance of inner ear fluids homeostasis and their biochemical integrity are essential for the well functioning of hearing and equilibrium. Alterations in women s hormonal levels during menstrual cycle, menopause, and pregnancy can cause inner ear homeostasis disorders and, thus, related hearing and vestibular symptoms. The aim of this research was to evaluate hearing and equilibrium in postmenopausal women. The participants were 27 postmenopausal women with ages ranging from 45 to 58 who were not or are not upon hormonal reposition. All of them were submitted to anamnesis, otorhinolaryngological examination, basic hearing evaluation, and vectoelectronystagmography. In relation to anamnesis, significant prevalence of symptoms as headache, insomnia, anxiety, and nausea was observed. The complaint of dizziness was observed in 66, 66 percent of the 27 participants, while the complaint of tinnitus was detected in 40,74 percent of them. As for hearing, 48,15 percent of the postmenopausal women presented alteration in their audiometric results, while in reference to equilibrium, 40,74 percent of them showed alterations in their vectoelectronystagmography results. So, from these results, it can be concluded that postmenopause women present complaints about dizziness and tinnitus as well as present some alterations in their hearing and equilibrium.